Taylor’s focal cortical dysplasia revisited: History, original specimens and impact - Kasper, Burkhard S. (Free Neuropathology, 2021)
50 years ago back in 1971, David C. Taylor and colleagues from England reported on a small series of surgical epilepsy cases proposing a new type of tissue lesion as a cause of difficult-to-treat focal epilepsy: a localized malformation of cerebral cortex. The lesion is now known as focal cortical dysplasia (FCD) Type II or Taylor’s cortical dysplasia. FCD II is not rare, and today is a frequent finding in neurosurgical epilepsy specimens. Medical progress has been achieved in that the majority of FCD II is diagnosed non-invasively by magnetic resonance imaging today. Detailed studies on FCD revealed that the lesion belongs to a spectrum of mTOR-o-pathies, thereby confirming the authors´ initial hypothesis of a relationship to tuberous sclerosis. Here, selected original materials from Taylor´s series are presented as virtual slides, supplemented by original clinical records, in order to give a first-hand impression of this milestone finding in neuropathology of epilepsy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Dysplasia; Epilepsy; FCD; History; Taylor